The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0370-44672007000400005
|View full text |Cite
|
Sign up to set email alerts
|

A qualidade das águas na região dos garimpos de topázio imperial na sub-bacia do rio da Ponte, Ouro Preto-MG

Abstract: Around the Ouro Preto region, State of Minas Eh, dissolved oxygen, electrical conductivity, turbidity, alkalinity, chloride, sulfate, metals (Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, Li, Mg, Mn, Mo, Na, Ni, Sc, Sr, Ti, V, Y and Zn) ResumoNa região de Ouro Preto observa-se significativa presença de garimpos de topázio. Essa atividade caracteriza-se pela utilização de técnicas rudimentares e sem controle de descarte dos rejeitos. Entre os danos causados ao meio físico e biótico estão o desmatamento; geração d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…The National Council for the Environment (CONAMA -Resolution 357, 2005) establishes a total Mn limit of 0.1 mg/l for class 1 waters (waters that can be used for human consumption after simplified treatment), 0.5 mg/l for class 3 waters (waters that can be used for human consumption after conventional or advanced treatment) and 1 mg/l of dissolved Mn for discharging effluents. However, research has demonstrated that Mn concentration in waters of mining and mine drainage regions, as well as industrial waste waters, exceed the recommended concentrations (Banks et al 1997;Sisinno 2003;Guimarães-Silva et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The National Council for the Environment (CONAMA -Resolution 357, 2005) establishes a total Mn limit of 0.1 mg/l for class 1 waters (waters that can be used for human consumption after simplified treatment), 0.5 mg/l for class 3 waters (waters that can be used for human consumption after conventional or advanced treatment) and 1 mg/l of dissolved Mn for discharging effluents. However, research has demonstrated that Mn concentration in waters of mining and mine drainage regions, as well as industrial waste waters, exceed the recommended concentrations (Banks et al 1997;Sisinno 2003;Guimarães-Silva et al 2007).…”
Section: Introductionmentioning
confidence: 99%